Born yesterday [videorecording (DVD)] - Mannheimer, Albert, 1913-1972; Holliday, Judy; Holden, William, 1918-1981; Crawford, Broderick, 1911-1986; St. John, Howard, 1905-1974; Oliver, Larry, 1880-1973; Brown, Barbara, 1901-1975; Rhodes, Grandon; Carleton, Claire, 1913-1979; Walker, Joseph B.; Hollaender, Friedrich; Kanin, Garson, 1912-1999 (Columbia classics., 1999)
A corrupt millionaire junk dealer, embarrassed by his girlfriend's lack of social sophistication, arranges to have her trained in a crash course in "culture." He is surprised and outraged when after becoming aware of her role as pawn in his crooked business deals, she refuses to cooperate.